Nugget mechanical properties of combination (rectangular and round) welded and soldered stainless steel wires - Zainab M Hasan; Fakhri A Ali (College of Dentistry/ University of Baghdad, 2014)
Background: This study aimed to compare the mechanical properties between four groups of newly fabricated combination wires according to their method of union, according to the gauges of wires and a comparison were made between them and their originals. Materials and method: A total of 60 stainless steel combination wires were fabricated , divided into four groups according to gauge of wires and their method of union, each of them with 15 samples, the groups were welded (0.016x0.022-0.016 and 0.016x0.022-0.018) and soldered (0.016x0.022-0.016 and 0.016x0.022-0.018), samples were made according to certain parameters which were : for the welded samples: length,weight, duration of pulsation and size of copper electrode tips used; for the soldered samples: length, weight, distaince from the heat source and duration of heat application Results: The descriptive statistics showed that the maximum value for ultimate force and ultimate tensile strength was for the soldered 0.016x0.022+0.018 inches combination wires, while the minimum was for the welded 0.016x0.022+0.016inches wires. Elastic modulus showed higher values for the soldered 0.016x0.022+0.016 and resiliency values for the welded 0.016x0.022+0.016 were the highest. Comparison between combination wires and their originals showed a decrease in the mechanical properties after soldering and welding. Conclusion: Higher gauge wires and soldering method of union showed better mechanical properties than the other groups and both soldering and welding method showed changes in the mechanical properties of the newly fabricated wires when comparing them with their originals.